Years of upheaval - Kissinger, Henry, 1923- (Boston : Little, Brown, 1982)
Years of Upheaval opens with Dr. Kissinger being appointed Secretary of State. Among other events of these turbulent years that he recounts are his trip to Hanoi after the Vietnam cease-fire, his efforts to settle the war in Cambodia, the Year of Europe, two Nixon-Brezhnev summit meetings and the controversies over arms control and détente, the military alert and showdown with the Soviet Union over the Middle East war, the subsequent oil crisis, the origins of shuttle diplomacy in the Middle East, the fall of Salvador Allende in Chile, and the tumultuous events surrounding Nixon s resignation. Throughout are candid appraisals of world leaders, including Nixon, Golda Meir, Anwar Sadat, King Faisal, Hafez al-Asad, Chairman Mao, Leonid Brezhnev, Willy Brandt, Helmut Schmidt, Georges Pompidou, and many more.
Includes bibliographical references and index.
Keywords: Kissinger, Henry, -- 1923-; Statesmen -- United States -- Biography; United States -- Foreign relations -- 1969-1974.